Osteoid Osteoma of the Femoral Neck Masquerading as Avascular Necrosis: A Diagnostic Dilemma and Management Success Story - Amit Kale; Sahil Chowdhary (Journal of Orthopaedic Case Reports)
Introduction: Osteoid osteoma is a benign bone tumor, accounting for 10–12% of benign bone lesions, most commonly affecting young adults aged 10–35 years. While typically presenting with night pain relieved by non-steroidal anti-inflammatory drugs, atypical locations like the femoral neck can mimic other conditions, such as avascular necrosis (AVN), complicating diagnosis. This case highlights the diagnostic challenge posed by overlapping symptoms and underscores the importance of advanced imaging for accurate diagnosis and timely management. Case Report: We present a case of a 21-year-old male who initially presented with persistent right hip pain. Initial magnetic resonance imaging revealed marrow edema in the right femoral neck with associated joint effusion, leading to a preliminary diagnosis of stress fracture and subsequent misdiagnosis of AVN. The patient’s symptoms persisted despite conservative management. After 6 months of continued symptoms, computed tomography (CT) imaging revealed a characteristic lucent lesion in the inferior cortex of the right femoral neck, confirming the diagnosis of osteoid osteoma. The patient underwent successful radiofrequency ablation (RFA) performed in three cycles. Conclusion: This case emphasizes the potential for osteoid osteoma to masquerade as AVN, particularly in young adults with hip pain. It demonstrates the superiority of CT imaging in detecting the characteristic nidus of osteoid osteoma and highlights the effectiveness of RFA as a definitive treatment modality.